A Review of Solo Taxonomy on Students’ Errors in High Mathematical Abilities in Calculating Definite Integral of Trigonometric Functions - Christinove, Rosa Mery; Mampouw, Helti Lygia (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
The aim of this research is to review students’ error in calculating the definite integral of trigonometric functions using Solo Taxonomy. This research is descriptive qualitative research. The results of the study show that the most errors done by the students are at the multi-structural level caused by the addition errors and the lack of subjects’ accuracy. Errors at the pre-structural level are the errors done by the subjectswho do not understand the purpose of the problems given. At the uni-structural level, the subjects make mistakes by applying the concept from the beginning of the problem. At the relational level, the subject uses a concept that is not common to solve problems but it has passed through several steps of completion. The results of this study can be a reference to anticipate and reduce students’ errors in calculating the definite integral of trigonometric functions.